Household Food Security Status and Child Health Outcomes in Kenya - Michelle M. Mwangi; Mercy G. Mugo (European Scientific Journal, ESJ, 2019)
Interminable access to sufficient, nutritious, and safely prepared food is a human right. Attributed to insufficient food and nutrient intake, malnutrition is a major health burden in developing economies that has maimed socioeconomic development. In children, undernourishment impairs the functioning of the immune system, increases susceptibility to diseases, and undermines physical and cognitive development. In Kenya, there exists a paucity of empirical corroboration of the effect of household food security status (HFSS) on child health outcomes. Using data drawn from the 2014 Kenya Demographic and Health Survey, this paper focuses on analyzing the causal link between HFSS and child health outcomes and to provide evidencebased policy recommendations to promote child health outcomes. We employed three measures of HFSS: households that lacked food/enough money to purchase food, the Reduced Coping Strategy Index (CSI), and the Food Consumption Score (FCS). The child health production function was estimated using the two-stage residual inclusion (2SRI) technique to control for potential endogeneity. The results indicate that households that lacked food/enough money to purchase food were significantly associated with stunted, wasted, and underweight growth in children. Similarly, the Reduced CSI was a significant determinant of stunted and underweight growth in children. However, the effect was insignificant relative to wasted growth. The findings also indicate that FCS contributes significantly to improvements in child health outcomes. Our evidence has the potential to inform policies on the promotion of child health outcomes. We recommend implementation of programs such as social assistance, integration of nutrition and WASH, and capacity-building to promote women’s knowledge of health, nutrition, and better child-care practices.